The Benefits of Teat Dipping as Prevention of Mastitis - Yanuartono Yanuartono; Alfarisa Nururrozi; Soedarmanto Indarjulianto; Hary Purnamaningsih; Dhasia Ramandani (Journal of Livestock Science and Production, 2020)
Mastitis is the major disease and the most costly disease of the dairy industry worldwide. One of the mastitis control programs that until now has been carried out and proven to be quite effective is the teat dipping method as a form of prevention. Various methods and uses of teat dipping solutions have been widely used and used for this purpose such as iodine, potassium permanganate, chlorhexidine, chlorhexidine gluconate chlorine, iodophor, sodium hypochlorite, lactic acid, phenolics and Dodecyl Benzene Sulfonic Acid (DDBSA). Pre milking and post milking teat disinfection have been recommended widely by veterinarians and adopted by dairy producers in increasing numbers. This procedure is simple to perform, economical, and effective in controlling contagious mastitis pathogens. More recently, teat dipping in association with good udder preparation reduced the rate of intramammary infections by environmental pathogens. This paper aims to provide a brief review of the benefits of teat dipping as a method of controlling the incidence of mastitis in dairy cows. Keywords: mastitis, teat dipping, pathogens, intramammary infections